ROAD GEOMETRIC ANALYSIS: CASE STUDY OF ROAD PANGKALAN PARI - KERTICALA - Kamaludin; Indrastuti (LEADER: Civil Engineering and Architecture Journal, 2024)
In order to facilitate the movement of people from the place of origin to the place of destination, adequate transportation facilities must be fulfilled, both land, sea and air. In general, land dominates more to support these activities, such as railroads, which are one of them. The existence of this journal is to analyze the horizontal alignment of the 9.4 km long pari-kertical road section. At coordinate point X = 200180.40 ; Y = 9239557.46 and ends at coordinates X = 201072.18 ; Y = 9239177.37. From the results of the calculation of the horizontal alignment of the existing field data at a bend with a speed VR = 60 km/hour, the radius at the bend is Rc = 716 m, the value for Ls (transition curve) = 50 m, Ts = 621.76.